2021
DOI: 10.1007/s00704-020-03473-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multivariate linear regression for reference evapotranspiration modeling in different climates of Iran

Abstract: The study aimed to evaluate the accuracy of empirical equations (Hargreaves-Samani; HS, Irmak; IR and Dalton; DT) and multivariate linear regression models (MLR1–6) for estimating reference evapotranspiration (ETRef) in different climates of Iran based on the Köppen method including arid desert (Bw), semiarid (Bs), humid with mild winters (C), and humid with severe winters (D). For this purpose, climatic data of 33 meteorological stations during 30 statistical years 1990–2019 were used with a monthly time step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…The RMSE/MAE and NMRSE are equal to 0.409/0.320 mm d −1 and 12.1%, respectively (Table 2). According to the literature, these values are considered very good to excellent in terms of accuracy [58]. Sunshine hours is a parameter that was computed according to FAO guidelines for missing data, utilizing Julian day and station latitude [33], which might be a limitation in terms of accuracy compared to direct measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RMSE/MAE and NMRSE are equal to 0.409/0.320 mm d −1 and 12.1%, respectively (Table 2). According to the literature, these values are considered very good to excellent in terms of accuracy [58]. Sunshine hours is a parameter that was computed according to FAO guidelines for missing data, utilizing Julian day and station latitude [33], which might be a limitation in terms of accuracy compared to direct measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Sharafi and Ghaleni compared the performance of six MLR models to empirical methods. They found that all the MLR models outperformed the latter [58]. The obtained RMSE values, ranging between 0.36 mm d −1 and 0.50 mm d −1 , were considered excellent, so that MLR was recommended for all climate types of Iran, from arid desert to humid [58].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A literature review of time series, empirical, and data-driven modeling techniques was conducted to simulate ETo e.g. Haung et al (2019); Fan et al (2018), Nourani et al (2019), Yu et al (2020), Sharafi and Ghaleni, (2021), Douna et al (2021). There have already been several conventional modeling techniques that have proven to be successful in modeling ETo using ANN Algorithm (Achite et al 2022;Gocić and Amiri, 2021;Nawandar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise [8] implemented an intelligent temperature and humidity monitoring system for remote environmental monitoring. [9] 1006 (2022) 012009 IOP Publishing doi:10.1088/1755-1315/1006/1/012009 2 evaluated the accuracy of linear regression equations based on meteorological data such as minimum and maximum temperature, relative humidity, wind speed, solar radiation, extraterrestrial radiation and vapor pressure deficit. In this study we estimate global solar radiation based on environmental variables (temperature, humidity, wind speed) by applying multiple linear regression analysis.…”
Section: Introductionmentioning
confidence: 99%